PENGARUH KEPRIBADIAN DAN KOMPETENSI GURU TERHADAP KINERJA GURU YANG DIMODERASI LINGKUNGAN KERJA DI MTS SEKECAMATAN WINONG KABUPATEN PATI - Sutomo, Y; Moh. Sururi Ma’ruf, 12.5202.0249 (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aimed to examine the influence of personality and competence ofteachers on teacher performance in MTs Sekecamatan Winong moderated Pati regencywith the work environment. The specific objectives of this study was to examine theinfluence of personality and competence of teachers on teacher performance aremoderated by the role of the working environment. The usefulness of this study is toclarify and extend previous research on the influence of personality and competence ofteachers on teacher performance are moderated working environment.This study used a sample of teachers in MTs Sekecamatan Winong Pati regencymuch as 121 teachers. Sampling techniques in this study is random sampling.Based on the results of the study can be summarized as follows personality doesnot affect the performance of teachers, teacher competence affect the performance of theteacher, the work environment does not affect the performance of the teacher, personalitynot influence on teacher performance is moderated by the working environment, and thereis the influence of teacher competence on teacher performance moderated by the workenvironment.Keywords: personality, teacher competence, work environment, the performance of teachers.